The influence of training, discipline, and innovation on the performance of members of the Regional National Crafts Council (Dekranasda) in Tanjungpinang City: A quantitative study - Afriyani, Nur; Indrayani, Indrayani; Indrawan, Mohamad Gita; Wibisono, Cablullah; Ngaliman, Ngaliman (Goodwood Publishing, 2023)
Purpose: This study examines the impact of innovation, discipline, and training on the performance of Tanjungpinang City members of the Regional National Crafts Council (Dekranasda). The research aims to identify how these factors interact and contribute to improving member performance through motivation as an intervening variable. Research Methodology: A quantitative descriptive design was employed using survey data from 130 Dekranasda members. Data collection was conducted through questionnaires, and the analysis utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS) and path analysis to evaluate direct and indirect effects of training, discipline, and innovation on motivation and performance. Results: The results indicate that workload had no significant direct influence The findings reveal that training has a significant effect on motivation, discipline, and performance. Discipline and innovation also significantly affect motivation and performance. Moreover, motivation itself strongly influences performance, mediating the effects of training, discipline, and innovation. The model achieved an adjusted R² of 0.984, indicating that 98.4% of performance can be explained by these factors combined with motivation. Conclusions: Training, discipline, and innovation play crucial roles in enhancing performance among Dekranasda members, with motivation acting as a central mediator. Limitations: The study is limited by its sample size, reliance on self-reported data, and focus on a single organizational context, which restricts generalizability. Contribution: This research provides empirical evidence on the interrelationships among training, discipline, innovation, and motivation in a regional crafts council context. The insights offer practical guidance for policymakers and practitioners in strengthening member performance through targeted training, effective discipline, and fostering innovation.